The impact of contact lens wear on ocular surface mucins using a novel clinical fluorescence imaging system. Issue 4 (August 2020) - Read, Michael L.; Navascues-Cornago, Maria; Keir, Nancy; Maldonado-Codina, Carole; Morgan, Philip B.
Highlights: Ocular surface mucins were imaged using fluorescein-tagged wheat germ agglutinin dye and a custom imaging system. Mucin density appeared greatest on the bulbar conjunctiva and lowest on the cornea. Contact lens wear reduced F-WGA dye binding across the ocular surface, with the most marked effect at the cornea. F-WGA associated fluorescence appeared reduced in the lid wiper region for symptomatic contact lens wearers. F-WGA imaging is a key tool in furthering our understanding of contact lens discomfort and ocular surface disease. Abstract: Purpose: Fluorescein-labelled wheat germ agglutinin (F-WGA) acts as a marker for ocular surface mucins. This clinical study sought to investigate whether the degree of F-WGA fluorescence observed at the ocular surface differed between symptomatic contact lens wearers, asymptomatic contact lens wearers and non-contact lens wearers, using a novel imaging system. Methods: Twenty-five participants (10 symptomatic contact lens wearers, 10 asymptomatic contact lens wearers and 5 non-contact lens wearers) attended a single study visit. Photographs of the cornea, bulbar and tarsal conjunctiva were captured following application of F-WGA solution. Results: The imaging system captured high-resolution images of F-WGA fluorescence at the ocular surface. The degree of fluorescence differed between the ocular surface regions ( p < 0.001). A significant difference in fluorescence was observed between participant groups for the cornea ( p = 0.01), with both the symptomatic and asymptomatic contact lens wearers showing lower fluorescence than the non-lens wearers. F-WGA associated fluorescence appeared diminished in the lid wiper region of the symptomatic lens wearers, compared to the asymptomatic group ( p = 0.025). Conclusion: The use of F-WGA as a clinical marker for ocular surface mucins allows an improved understanding of their distribution across the ocular surface. Contact lens wear appears to negatively impact mucin density across the ocular surface, with the most marked effect on the cornea. F-WGA fluorescence appeared diminished in the lid wiper region for the symptomatic contact lens wearing group, indicating that mechanical interaction in this region may play a role in the aetiology of contact lens discomfort. Given the ability of F-WGA to disclose mucin distribution across the ocular surface it is likely to be a key clinical tool in furthering our understanding of (i) the aetiology of contact lens related discomfort, (ii) contact lens designs/materials to minimise interaction with the ocular surface and (iii) dry eye disease and other ocular surface diseases.